PENGARUH PENAMBAHAN VITAMIN EKE DALAM PAKAN GUNA MENINGKATKAN KEMATANGAN GONAD KEPITING BAKAU (Scylla serrata) - Yosafat Ngongo; Agnette Tjendawangi; Yulianus Linggi (Jurnal Akuatik, 2019)
A research on crab’s gonad maturation had been conduncted by adding vitamin E in to their feed, with a view to knowing the stage of gonad maturity. The aim of this research is to know the maturity stage of gonad by observing the colour change as indicator of TKG with the addition of vitamin E in feed as much 20, 25 and 30 ml . kg -1 of feed. The research was conducted with completly randomized design (CDR) with 4 treatments and 3 repatitions.The results showed that the addition of vitamin E in to the feed as much 30 ml . kg -1 of feed can increase TKG (gonad maturity stage)to reaches stage IV and addition vitamin E as much 25 ml . kg -1 of feed can stimulate crab gonad up to TKG III, While the addition of vitamin E 20 ml . kg -1 of feed and control was only able to stimulate crab’s gonad reach to stage II. Based on these results it is concluded that the more vitamin E is added (up to dose of 30 ml . kg -1 of feed) in to the feed then the maturity rate of gonad crab’s is increasing. Keywords: gonad maturity, gonad colour, vitamin E, mud crab